Bring the outside in : the essential guide to cacti, succulents, planters and terrariums - Bradley, Valerie (Bantam Press, 2016)
With stunning photography and expert step-by-step tips, Bring The Outside In reveals everything you need to know to help your plants thrive, from dramatic statement foliage and miniature citrus trees to table-top terrariums and hanging planters. With chapters on orchids, cacti, herb gardens and chilli plants, your home will be flourishing in no time.